2018
DOI: 10.5152/tjar.2018.20280
|View full text |Cite
|
Sign up to set email alerts
|

Can Amantadine Ameliorate Neurocognitive Functions After Subarachnoid Haemorrhage? A Preliminary Study

Abstract: Objective: Aneurysmal subarachnoid haemorrhage (SAH) may have devastating effects on patients. Motor and neurocognitive impairments may arise depending on the location and grade of the SAH. Although the effects of amantadine on neurocognitive function after traumatic brain injury have been widely studied to the best of our knowledge, their effects on recovery from SAH in humans have not been studied. The present study aimed to evaluate how amantadine influences improvement in neurocognitive function in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…Recently, Akcil et al ( 2018 ) studied the effects of amantadine on neurocognitive function recovery from subarachnoid hemorrhage (SAH) over 6 months. A group of five patients received the standard-of-care plus amantadine for 30 days, while the other seven patients received the standard treatment only on the first and fifth days and at the third and sixth months after admission.…”
Section: Preclinical and Clinical Evaluation Of Amantadine’s Non-canomentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Akcil et al ( 2018 ) studied the effects of amantadine on neurocognitive function recovery from subarachnoid hemorrhage (SAH) over 6 months. A group of five patients received the standard-of-care plus amantadine for 30 days, while the other seven patients received the standard treatment only on the first and fifth days and at the third and sixth months after admission.…”
Section: Preclinical and Clinical Evaluation Of Amantadine’s Non-canomentioning
confidence: 99%
“…A group of five patients received the standard-of-care plus amantadine for 30 days, while the other seven patients received the standard treatment only on the first and fifth days and at the third and sixth months after admission. The data suggested that adding amantadine to the standard treatment during the early period of SAH may improve neurocognitive function recovery evaluated using the Coma Recovery Scale-Revised (CRS-R) and Disability Rating Scale (DRS) (Akcil et al 2018 ).…”
Section: Preclinical and Clinical Evaluation Of Amantadine’s Non-canomentioning
confidence: 99%
See 1 more Smart Citation
“…While amantadine was found not beneficial at all for overall cognition in traumatic brain injured patients in a multisite, randomized, controlled trial, published in September 2018, 5 it was found effective in enhancing neurocognitive function after TBI in another prospective, randomized controlled trial taking place in Turkey and published in the same year. 6 Systematic reviews discussing the effectiveness of amantadine in TBI were not easily done because the definition of TBI is not consistent across research. It changes according to specialties and circumstances.…”
mentioning
confidence: 99%
“…However, conflicting findings from clinical trials regarding its effectiveness for reducing cognitive and behavioral problems have hindered advances in justifying this hypothesis. While amantadine was found not beneficial at all for overall cognition in traumatic brain injured patients in a multisite, randomized, controlled trial, published in September 2018, 5 it was found effective in enhancing neurocognitive function after TBI in another prospective, randomized controlled trial taking place in Turkey and published in the same year 6 …”
mentioning
confidence: 99%